"I Love My Body; I Love It All" : Body Positivity Messages in Youth-Oriented Television Series. Issue 1 (2nd January 2023) - Maes, Chelly; Vandenbosch, Laura
ABSTRACT: Traditionally, content analyses of body image (BI) messages in youth-oriented series have focused on negative messages. Thus, studies have not addressed the potential for youth-oriented series to promote positive BI (PBI). Using the main principles of the General Learning Model, this study fills this gap in the literature through a content analysis of the PBI messages in six youth-oriented television series. A total of 126 characters (52% male, 48% female) and 3, 151 scenes across 65 episodes were coded. We further paid attention to the co-occurrence between PBI and negative BI (NBI) messages, and to who promoted PBI messages (i.e., character gender and body size). The results indicate that a PBI message occurred in a youth-oriented television series twice per episode. Also, NBI and PBI messages co-occurred. This underlines the complexity of the television landscape and implies that scholars should focus on both NBI and PBI, instead of exclusively examining NBI messages and their impact on adolescents' BI. Further, the distribution of PBI messages did not vary by character gender. Lastly, characters with below-average body sizes were more likely to convey PBI messages.